Impact of Corona Virus (COVID-19) Pandemic on Small and Medium Scale Enterprises (SMEs) in Nigeria: A Critical Case Study: Array - Aderemi, Timothy Ayomitunde; Ojo, Lucas B.; Ifeanyi, Okoh Johnson; Efunbajo, Samuel Adekunle (Acta Universitatis Danubius. Œconomica, 2020)
The aim of this study is to investigate the impact of COVID-19 pandemic on selected small and medium enterprises in Nigeria, with a view to ascertaining the impact of lockdown on SMEs engaging in three essentials- food and consumables, pharmaceuticals, oil and gas in Sango-Ota industrial area of Ogun state, Nigeria. Data were collected with the administration of structured set of questionnaire on 100 SMEs which were selected purposively. Findings from the analysis showed that the enterprises experienced moderate reduction in production and sales during the lockdown. However, the surveyed enterprises experienced a spike in reduction of contracts and deliveries. In view of the above, the study makes the following recommendations for the policy makers and all stakeholders in SMEs in Nigeria that: pandemic is still ongoing, a spike reduction in operations and sales of SMEs will metamorphose into cash-trap. This would increase the vulnerability of SMEs in Nigeria to other external shocks. Therefore, the government should set aside emergency fund targeting SMEs in the country. Deferment of taxes or waiver of taxes, lower of interest rate could also be embarked on by the appropriate policy makers to make SMEs remain afloat during and after COVID-19 pandemic.